If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4a + 9 = 25 Reorder the terms: 9 + -4a = 25 Solving 9 + -4a = 25 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4a = 25 + -9 Combine like terms: 9 + -9 = 0 0 + -4a = 25 + -9 -4a = 25 + -9 Combine like terms: 25 + -9 = 16 -4a = 16 Divide each side by '-4'. a = -4 Simplifying a = -4
| -3+39+15x=3 | | 8v=7 | | 5x-7=50+20 | | -2x^2+7x-16=0 | | 3x+7=12x-2 | | 4x^3+4x^2-15x-18=0 | | 5t^2-5t=0 | | 6(x-6)=2(x-2) | | 5a^2-13a-28=0 | | 12x+20-6x+8x=36x-64+20x | | (2n+4)(2n-1)-1=19 | | x-5(x+2)=x+3(3-2y) | | -9r+12= | | (x+7)=0 | | 3x-45x-12=21+3-67x | | 7x-8(x+1)=0 | | 2t^2+t-5=0 | | -3x+10-7x+20x+6=16x+2-5x-3x+10-2x | | (2x-y-1)dx+(y-1)dy=0 | | 9+r=6 | | 4(x+7)=5x+8 | | 6x^2+1x-23=0 | | cos(t)=3 | | 16x^2-y^2-32x-6y+11=68 | | 7=-3c-2-24 | | d-4.6=-11.6 | | 2x-10+3x-7+5x=3x+3-3+3x-7+5x | | 35-5(2x-5)+20=-68 | | 0.2+1= | | X(over)4-9=3 | | -6x+10(-6)=-18 | | -2x-3+8x-18+5x=15-20-2x-3 |